(3OjhGf GdTQja GdQVjs - (3eMeO Hf GdMSjf Hf ehSi GdYdhj GdMSjfj GdehShj, GdTQja GdQVj , CHh GdMSf,J (B406 (3g` s
(3ChdgG (B:s
(3eHJhQ hChd GdehLhO efgG(B: (3jgGH Sjac eUbhdkG heNJVHkG hCgjH GdTYQ TjH ZjQ eNVhH s
(3BNQgG (B:s
(3eHJhQ CjVkG hjfJgj Hbhdg(B: (3hbO SdeJg Taha GdTeGd hQqUY obWQjg bWQ GdQeGe s
(3fSNI QGHYIs
(3hQOJ CjVkG JMJ Qbe (B2191(3, (B2244(3, (B70(3, (B725s
(3ZjQ eQJHI Ydi GdbhGajs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B261s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B128 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B794s
Keywords: (3GdCOHs